Global natural gas market integration in the face of shocks: Evidence from the dynamics of European, Asian, and US gas futures prices - Markos Farag; Samir Jeddi; Jan Hendrik Kopp (Institute of Energy Economics at the University of Cologne (EWI), 2023)
This paper analyzes the integration of the American, European, and Asian natural gas markets over the period 2016-2022, with a focus on how the demand shock caused by the COVID-19 pandemic and the supply shock caused by geopolitical tensions in the European market affected this integration. We also examine which regional market is leading in reflecting new information and shocks into the market price. Our analysis indicates that the market integration process has been impacted by external shocks, leading to a decrease in the degree of integration between the European and Asian markets. Additionally, we find that the American market is no longer integrated with the other two markets after the supply shock, potentially due to the US's congested and fully utilized LNG infrastructure. Our analysis also shows that the gas price differentials adjust asymmetrically in response to disturbances, suggesting that markets respond differently to positive and negative shocks. Moreover, we show that the lead/lag relationship changes over time and exhibits a dynamic behavior. Finally, we discuss the fundamental changes in the global gas market that align with our empirical results.
Keywords: C32; D40; D58; F21; F41; G13; G14; L95; Q35; Q41; 330; Natural gas markets; Market integration; Threshold Co-integration; Time-varying causality